2017
DOI: 10.13168/cs.2017.0044
|View full text |Cite
|
Sign up to set email alerts
|

EFFECTS OF NiO LOADING AND PRE-CALCINATION TEMPERATURE ON NiO-SDCC COMPOSITE ANODE POWDER FOR LOW-TEMPERATURE SOLID OXIDE FUEL CELLS

Abstract: The microstructural and thermal characteristics of NiO-samarium-doped ceria carbonate (NiO-DCC) composite powders have been explored in terms of NiO loading and pre-calcination temperature. NiO-SDCC composite powders were intimately mixed via fast ball-milling using different NiO loadings (50-70 wt. %) and subjected to various pre-calcination temperatures (600-800°C). Subsequently, the pre-calcined powders were then used to fabricate composite pellets using a uniaxial press and sintered at a low temperature of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 30 publications
(57 reference statements)
1
4
0
Order By: Relevance
“…These observations are kept settlement within the acceptable range (32.3% to 38.7%) and have been reported earlier in the previous paper [21]. Ng et al, (2016) have suggested that the porosity of the cathode within 20% to 40% is recommended for enhancement of electrochemical performance for LTSOFC [14].…”
Section: Microstructure Analysissupporting
confidence: 84%
See 1 more Smart Citation
“…These observations are kept settlement within the acceptable range (32.3% to 38.7%) and have been reported earlier in the previous paper [21]. Ng et al, (2016) have suggested that the porosity of the cathode within 20% to 40% is recommended for enhancement of electrochemical performance for LTSOFC [14].…”
Section: Microstructure Analysissupporting
confidence: 84%
“…Meanwhile, prior research work revealed the presence of impurities or secondary phases from SSC such as strontium carbonate (strontionite), SrCO3, and strontium cobalt carbonate SrCoCO3 towards the structural stability and performance of LTSOFC need to be clearly investigated [14]. Identified SSC-SDC cathodes of SOFC become unstable in reduction atmospheres, which have been affected due to the occurrence of the decomposition process of SSC to strontium oxide (SrO) and samarium oxide (Sm2O3), throughout the performance.…”
Section: Introductionmentioning
confidence: 99%
“…From the observation, ascribed Ag as an additive element has been promoting on the better powder distribution with all the elements remain detectable and clearly perceived after the addition of 3 wt.% Ag content. Unfortunately, lithium (Li) elements accredited from the composite cathode of LSCF-SDCC and LSCF-SDCC-Ag were not discovered by the EDS analysis, due to low atomic mass property of lithium element [5]. The result discussed earlier has demonstrated that all the critical elements in LSCF-SDCC-Ag composite cathode powder have been homogeneously mixed and well-distributed powder has successfully achieved via HEBM method.…”
Section: Resultsmentioning
confidence: 99%
“…The homogeneity of elements is essential as each element contributes to the electrochemical reactions occurred in the cathode. HEBM method in this research has successfully produced the homogenously dispersed powders of LSCF-SDCC-Ag composite cathode [5,11].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation